2022
DOI: 10.3389/fmicb.2022.978502
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Dimetridazole and Ribavirin to disarm Pseudomonas aeruginosa virulence by targeting the quorum sensing system

Abstract: Pseudomonas aeruginosa relies on its complex cellular regulatory network to produce a series of virulence factors and to cause various acute and chronic infections in a wide range of hosts. Compared with traditional antibiotics which frequently accompany with widespread antibiotic resistance, crippling the virulence system of bacteria is expected to be a promising anti-infective strategy. In this study, Dimetridazole and Ribavirin, which had poor antibacterial activities on P. aeruginosa reference isolate PAO1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…Recent studies showed these compounds inhibited the growth of Clostridium difficile in vitro . In addition, dimetridazole was found to decrease Pseudomonas aeruginosa virulence by targeting the quorum sensing system . Furazolidone has been used in the treatment of certain bacterial and protozoan infections in human and animals for more than 60 years. , It displayed potent antiproliferative properties in a series of acute myeloid leukemia (AML) cells by inhibiting leukemia fusion proteins …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed these compounds inhibited the growth of Clostridium difficile in vitro . In addition, dimetridazole was found to decrease Pseudomonas aeruginosa virulence by targeting the quorum sensing system . Furazolidone has been used in the treatment of certain bacterial and protozoan infections in human and animals for more than 60 years. , It displayed potent antiproliferative properties in a series of acute myeloid leukemia (AML) cells by inhibiting leukemia fusion proteins …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study by Yuan et al , a combination of dimetridazole and ribavirin had no significant effect on the growth of P. aeruginosa PAO1 at concentrations lower than 244.2 μg/mL ( Yuan et al, 2022 ). These results suggest that dimetridazole and ribavirin at routinely used concentrations had poor antibacterial activity against P. aeruginosa PAO1 but might inhibit the quorum sensing (QS) system.…”
Section: Discussionmentioning
confidence: 99%
“…One of the medications explored for their antimicrobial activity is ribavirin. It has been reported that ribavirin successfully protected Caenorhabditis elegans and mice from P. aeruginosa infection ( Yuan et al, 2022 ). Ribavirin, an early-stage antiviral drug, has unique antimicrobial activities, especially against P. aeruginosa and Candida albicans ( C. albicans ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aeruginosa, farklı yerlerden izole edilebilen ve klinikte önemli bir enfeksiyon kaynağı olan Gram negatif fırsatçı bir patojen bakteridir [29,30]. Genom yapısı ve hücre iletişim mekanizması [quarum sensing-QS], virülans ve direncin gelişmesinde etkili bir özellik olarak kabul edilmiştir [31,32].…”
Section: Sonuç Ve Tartişma İzolatların Antibiyotik Duyarlılıklarıunclassified